Introduction to Information Technology and Independence Based on Prophetic Values at Sanggar Bimbingan Indonesia in Malaysia - Laksana, Sigit Dwi; Priatna, Yolan; Albanjari, Fatkhur Rohman; Kholis, Kholis; Widianingrum, Watik (International Journal on Advanced Science, Education, and Religion, 2025)
This community service program was conducted at Sanggar Bimbingan At Tanjil, Lembah Jaya, Selangor, Malaysia, with the aim of introducing information technology literacy and promoting economic independence based on prophetic values among children and parents of Indonesian migrant workers. The program applied a qualitative participatory approach, involving direct observation, interviews, and training workshops to identify and address the community’s specific needs in digital literacy, financial management, and moral education. The intervention included workshops on healthy internet use, family financial literacy, and the internalization of prophetic values such as honesty, responsibility, and diligence. Results showed that participants demonstrated improved understanding and skills in utilizing digital technology responsibly, managing finances wisely, and applying ethical principles in daily life. Despite challenges related to limited facilities and parental involvement, the program effectively strengthened community awareness and fostered collaboration between lecturers, students, and local leaders. In conclusion, the integration of technology education, financial literacy, and prophetic ethics offers an effective model for empowering migrant communities to achieve sustainable independence in both digital and economic aspects